Systemic immune inflammation index is a valuable marker for predicting hemodialysis patients with depression: a cross-sectional study - Han, Xi-xi; Zhang, Hui-ying; Kong, Jing-wen; Liu, Yu-xin; Zhang, Ke-ren; Ren, Wen-ying (Frontiers in Psychiatry, 2024)
Objective： Maintenance hemodialysis(MHD) patients suffer from enormous physical, mental stress and poor quality of life, so an increasing number of patients are in a long-term state of depression. A prominent feature of MHD patients is chronic persistent inflammation, which is also an important mechanism for the onset of depression. Therefore, finding economically convenient inflammatory markers to predict and diagnose the onset of depression in MHD patients is of great value. As a novel inflammatory marker, systemic immune inflammation index(SII) can more comprehensively reflect the inflammation and immunity level of patients. This study aims to explore the relationship between SII and depressive symptoms in MHD patients.Methods：A cross-sectional study was conducted on 206 MHD patients from three dialysis centers. Based on the Hospital Anxiety and Depression Scale(HADS) scores, patients were divided into non-depression and depression groups. Inter group comparison and multivariate logistic regression analysis were performed to determine whether SII is an independent risk factor for depression in MHD patients. Receiver operating characteristic(ROC) curve was used to evaluate the predictive value of SII on depression symptoms in MHD patients.Results：According to the HADS scale score, 38.83% of the included patients were in a state of depression. After adjusting for all confounding factors, MHD patients with SII>963.93 had a 4.709 times higher risk of depression than those with SII≤478.32 (OR=4.709, P<0.01). ROC analysis showed that SII>685.11 was the best cutoff value for MHD depression patients, and the area under the curve (AUC) was 0.681.Conclusions：High SII is an independent risk factor for depressed MHD patients and an ideal inflammatory marker for predicting and identifying depression in MHD patients as assessed by the HADS scale.